András Róna-Tas Language and History. Contributions to comparative Altaistics; Bulletin of the Institute for the Study of North Eurasian cultures, Hokkaido University (Hoppo Bunka Kenkyu), vol. 17 - Halén, Harry (Finnisch-Ugrische Forschungen, 1987)
.